External auditory canal carcinoma with an unusually extensive invasion - Shahbaz, Haania; Tahir, Munira; Junaid, Tehmina; Shakir, Najwa; Ahmed, Zeba (Journal of the Pakistan Medical Association, 2023)
External auditory canal carcinoma, while starting out as a seemingly benign condition, if left untreated can have an aggressive course of disease and involve multiple lower cranial nerves. Squamous cell carcinoma remains the most frequent histological type of malignant neoplasm of the external auditory canal and temporal bone. Here we describe a patient with a history of chronic suppurative otitis media with an extensive spread, the tumour was reaching from the skull base to the oropharynx involving neurovasculature along with soft tissues and bones, as well as the cerebellum. The involvement of the recurrent laryngeal and hypoglossal nerves were the most unusual presentation here. The case differed from all previous reported cases as the spinal accessory nerve was to spared. Surgery and radiotherapy are the treatment options but for the inoperable cases presenting with an already poor prognosis, concomitant radiotherapy is the only choice.